2021
DOI: 10.1017/s0022215121002565
|View full text |Cite
|
Sign up to set email alerts
|

Intracapsular tonsillectomy versus extracapsular tonsillectomy: a safety comparison

Abstract: Objective Post-tonsillectomy haemorrhage remains a significant complication despite modifications of technique and instrumentation. Intracapsular tonsillectomy spares the capsule as a protective barrier for underlying blood vessels and musculature. Its efficacy in children with sleep-disordered breathing has been established, along with lowered rates of haemorrhage and pain, but research pertaining to adults and for recurrent infections has been limited. Method This retrospective study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…In a more recent retrospective study reviewing 730 patients, both adults and pediatrics, the postoperative bleeding was compared between ICT and ECT using the Coblator. Again, a significant decrease in the rate of bleeding was observed in the ICT group (0.3% vs. 2.1%; P = 0.025) 23 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In a more recent retrospective study reviewing 730 patients, both adults and pediatrics, the postoperative bleeding was compared between ICT and ECT using the Coblator. Again, a significant decrease in the rate of bleeding was observed in the ICT group (0.3% vs. 2.1%; P = 0.025) 23 .…”
Section: Discussionmentioning
confidence: 79%
“…This is a significant improvement in the safety of tonsillar surgery. The relation of age to the risk of post-tonsillectomy bleeding is well known in the literature, showing a persistent higher incidence in adults compared to children 2 , whether undergoing ECT or ICT 23 . Looking solely at the pediatric age group, it was previously reported that the older the child, the higher the risk of postoperative bleeding; 1.9% for children < 5 yo, 3.0% for children 5-15 yo, and 4.9% for 16 yo and older 2 , but that was in patients who underwent ECT.…”
Section: Discussionmentioning
confidence: 97%
“…The included studies consisted of 3 RCTs using a with‐in patient design, 29 , 30 , 38 5 RCTs using a between‐patient design, 32 , 33 , 34 , 41 , 45 1 prospective cohort study, 40 and 8 retrospective cohort studies. 31 , 35 , 36 , 37 , 39 , 42 , 43 , 44 Across the 17 studies, a total of 1996 patients underwent CIT. The comparator arms included total tonsillectomy using plasma ablation (9 studies, 29 , 30 , 31 , 34 , 35 , 36 , 40 , 41 , 43 n = 1100), electrocautery (4 studies, 32 , 33 , 38 , 45 n = 155), cold steel (2 studies, 37 , 44 n = 77), electrocautery or plasma ablation (1 study, 42 n = 1800), any nonplasma ablation device (1 study, 35 n = 1216) and nondefined device (1 study, 39 n = 217).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies included pediatric patients, 30 , 31 , 32 , 33 , 34 , 36 , 39 , 40 , 41 , 42 , 44 3 included both adults and pediatric populations, 37 , 43 , 45 2 studies included adult patients, 29 , 38 and 1 did not report on age. 35 The primary indication for all tonsillectomy procedures was obstructive (without history of recurrent infective indications) in 6, 32 , 33 , 34 , 37 , 39 , 45 infective in 2, 29 , 30 and mixed obstructive and/or infective in 7 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation